2007
DOI: 10.1016/j.drugalcdep.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral economics of will in recovery from addiction

Abstract: Behavioral economic studies demonstrate that rewards are discounted proportionally with their delay (hyperbolic discounting). Hyperbolic discounting implies temporary preference for smaller rewards when they are imminent, and this concept has been widely considered by researchers interested in the causes of addictive behavior. Far less consideration has been given to the fact that systematic preference reversal also predicts various self-control phenomena, which may also be analyzed from a behavioral economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 85 publications
0
26
1
5
Order By: Relevance
“…They found that, compared to control subjects, cocaine users displayed a lower probability of inhibiting their responses and required more time to inhibit responses to stop signals. A more recent study also observed prolonged SSRT in chronic methamphetamine users than controls (Monterosso et al, 2005). Other studies have documented the acute effects of cocaine and alcohol (Fillmore and Rush, 2001;Mulvihill et al, 1997) on response inhibition.…”
Section: Stop-signal Task As a Tool To Study Response Inhibitionmentioning
confidence: 75%
See 1 more Smart Citation
“…They found that, compared to control subjects, cocaine users displayed a lower probability of inhibiting their responses and required more time to inhibit responses to stop signals. A more recent study also observed prolonged SSRT in chronic methamphetamine users than controls (Monterosso et al, 2005). Other studies have documented the acute effects of cocaine and alcohol (Fillmore and Rush, 2001;Mulvihill et al, 1997) on response inhibition.…”
Section: Stop-signal Task As a Tool To Study Response Inhibitionmentioning
confidence: 75%
“…The two behavioral indices, the inhibitory function and SSRT, have been widely used to describe impaired inhibitory control in people with neurological (Aron and Poldrack, 2005;Aron et al, 2003;Dimitrov et al, 2003;Reiman et al, 1997;Stewart and Tannock, 1999) or psychiatric conditions, including patients with SUDs (Armstrong and Munoz, 2003;Badcock et al, 2002;Dimoska et al, 2003;Li et al, 2006c;Monterosso et al, 2005;Oosterlaan and Sergeant, 1996;Overtoom et al, 2002;Rubia et al, 1998;Schachar et al, 1995). used a choice reaction stop-signal task to study inhibitory control in chronic cocaine users .…”
Section: Stop-signal Task As a Tool To Study Response Inhibitionmentioning
confidence: 99%
“…When they do, aversive items are usually electric shocks or emission of an aversive sound (Monterosso & Ainslie, 2007), generally consequences outside the daily context of human subjects.…”
Section: Nature Of the Stimuli: Appetitive And Aversive In Delay Discmentioning
confidence: 99%
“…Numerous studies have shown that addicts tend to be more impulsive than nonaddicts (see Acton, 2003;Bickel & Marsch, 2001;Iacono, Malone, & McGue, 2008;Monterosso & Ainslie, 2007;Olmstead, 2006;Verdejo-Garcia, Lawrence, & Clark, 2008). In much the same way that impulsivity seems characteristic of other types of addiction, a small number of studies suggest that impulsive behavior might also be characteristic of individuals who use the Internet to excess.…”
mentioning
confidence: 99%